Outcomes of eye injuries with retained intraocular foreign material at Groote Schuur Hospital, Cape Town. (October 2016) - Rice, James Clarke; Steffen, Jonel
Background: Retained intraocular foreign body (IOFB) is a specific subgroup of open globe injury which is often preventable with appropriate use of eye protection. We describe the spectrum of injuries resulting in IOFB, outcomes and complications following vitrectomy surgery and context specific risk factors which may influence outcomes at our hospital. Methods: Retrospective cohort study of 43 consecutive cases of IOFB that underwent vitrectomy surgery. Results: The median age was 34.6 years and 95.3% were male. The presenting visual acuities ranged from 6/6 (LogMAR 0.00) to Perception of Light (PL) with a median of Hand Motions (HM) (Interquartile Range (IQR) 6/24-HM). Hammering metal was the most common cause of injury (44.2%); 72% of injuries occurred while performing premeditated high-risk activities. The foreign body was metallic in 76.7% of cases and penetrated the cornea in 69.8% of cases. Lens injury occurred in 65.1%. The retina was impacted in 36 cases (83.7%), four of which impacted the macula. Macula impact was associated with poor visual outcome ( p = 0.049, Fisher's exact). Four cases (9.3%) had endophthalmitis. The median final visual acuity was 6/24 (IQR 6/9–6/60). Visual acuity improved in 63.4.0%. Ten cases (23.8%) were worse than 3/60. Better presenting vision was associated with better visual outcomes ( p = 0.049, Fisher's exact). The Ocular Trauma Score predicted outcomes well in better prognosis categories but underestimated final visual outcomes in the poor prognosis category. Central corneal scarring contributed to reduced visual outcomes. Conclusion: The majority of IOFB injuries are preventable with appropriate use of eye protection. Visual outcomes are better than other causes of open globe injury. Resource constraints contribute to suboptimal final visual outcomes.